Compound mixtures based on hydrolyzed Polyacrylonitrilereducing soil electrical resisctivity - M. A. Drako; S. M. Baraishuk; I. A. Pavlovich (Известия высших учебных заведений: Проблемы энергетики, 2021)
THE PURPOSE. The purpose of the article is to define the reasons to improve the system of grounding devices design. Author studies technical decisions that reduce grounding resistance values. Results are given researches how a mineral conductive mixture, that normalizes grounding, influences a seasonal coefficient. Analysed the results of the experimental surveys. Аlso evaluates a test grounding devise’s resistance decrease compared to the resistance decrease of a control grounding device. METHODS. While solving the above problem, a number of field experiments were carried out to measure the resistance values of experimental circuit grounding devices after their near-electrode soil space had been treated with the mixture that improves the resistance of a grounding wire. RESULTS. The composition of the mixture that normalizes (reduces) soil electrical resistivity has been developed, it has contained hydro-stabilizing and lowdispersed conducting additives. There has been proposed the analytical expressions to evaluate equivalent soil electrical resistivity values after aporton of soil had been submitted by the mineral conducting mixture. CONCLUSION. The use of the mixtures based on hydrolyzed polyacrylonitrile is most effective together with the grounding wires buried in soil no deeper than the soil freezing depth that is located in the soil layers with maximum seasonal fluctuations, and will increase with the increase of the contact area of such grounding wires with the soil treated with hydrolyzed polyacrylonitrile. Additional decrease of a seasonal coefficient for the vertical compound grounding wires apparently is due to the mixture influencing their parts mounded near the ground surface. The use of complex mixtures containing both hydro-stabilizing additives and low-dispersed conducting substances allows up to three times decrease of the resistance values of a grounding device compared to a control grounding device, it allows to even seasonal fluctuation of resistance of a grounding device, and to decrease mounting capital investment for a grounding device by means of the decrease of the number of the electrodes and the territory on which they are located.